Exploring Dimensions of Spiritual Faithfulness in Church Ministry: A Narrative Study of Senior Pastor’s Ministry - Dadang Irawan; Rudy Pramono; Oki Hermawati; Erwin Santosa; Wylen Djap (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Faithfulness is often a virtue that sustains a mission of service. This study aimed to tell the experience one of the important actors (participants), a pastor. What are the dimensions that can build a faithful construction, especially in church services based on the experiences of participants. In a religious context, faithfulness has a different dimension, namely a transcendental dimension that does not stand alone, but is also influenced by a horizontal perspective which can be explained by the theory of stewardship. When stewardship is understood horizontally, the highest measurement of a relationship tends to be welfare and harmony. It gets reinforced by the vertical dimension where God becomes the authority of truth and becomes the reason to keep serving, especially serving faithfully. This study tries to frame the story about the phenomenon of faithfulness dimension in church ministry with a narrative approach. This study seeks to show how life of a pastor who uses faithfulness as the main pillar of his ministry.